Application of human factors at hybrid meetings: facilitating productivity and inclusivity. Issue 6 (July 2022) - Ellis, Ricky; Goodacre, Tim; Mortensen, Neil; Oeppen, Rachel S; Brennan, Peter A
Abstract: The COVID-19 pandemic has resulted in the widespread use of virtual meetings and conferences. As the healthcare sector attempts to return to normality, face-to-face meetings have started to resume. However, ongoing travel restrictions, risk of viral transmission, the Omicron variant, and requirements for self-isolation, have necessitated the use of novel hybrid meeting formats. These enable participants to attend either in person or virtually using various online platforms such as Microsoft Teams and Zoom. Well organised and facilitated hybrid meetings can combine the advantages of in-person meetings with virtual participation, although the dynamics of communication between attendees is considerably different. This article discusses the benefits and pitfalls of the hybrid format, the human factors that impact productivity and inclusivity, and how to address them in future meetings.